2016
DOI: 10.1139/apnm-2015-0479
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and energy intake — skeletal muscle mass is the strongest predictor of food intake in obese adolescents: The HEARTY trial

Abstract: There has been renewed interest in examining the relationship between specific components of energy expenditure and the overall influence on energy intake (EI). The purpose of this cross-sectional analysis was to determine the strongest metabolic and anthropometric predictors of EI. It was hypothesized that resting metabolic rate (RMR) and skeletal muscle mass would be the strongest predictors of EI in a sample of overweight and obese adolescents. 304 post-pubertal adolescents (91 boys, 213 girls) aged 16.1 (±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
52
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 59 publications
9
52
0
4
Order By: Relevance
“…Further confirmation of a positive association between energy intake with FFM, but not FM, can be derived from studies in adults 4-6 as well as in overweight and obese adolescents. 7 Taken together, these findings have strengthened the argument of Lissner et al 2 that 'research that focuses on the relationship between energy intake and obesity is misplaced because energy requirement appears to be a direct function of …”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Further confirmation of a positive association between energy intake with FFM, but not FM, can be derived from studies in adults 4-6 as well as in overweight and obese adolescents. 7 Taken together, these findings have strengthened the argument of Lissner et al 2 that 'research that focuses on the relationship between energy intake and obesity is misplaced because energy requirement appears to be a direct function of …”
mentioning
confidence: 66%
“…Further confirmation of a positive association between energy intake with FFM, but not FM, can be derived from studies in adults [4][5][6] as well as in overweight and obese adolescents. 7 Taken together, these findings have strengthened the argument of Lissner et al 2 that 'research that focuses on the relationship between energy intake and obesity is misplaced because energy requirement appears to be a direct function of lean mass rather than of adiposity'. Indeed, the predictive power of FFM on energy intake provides one explanation as to why people with obesity, on average, tend to eat more than lean people, given that the development of obesity is accompanied not only by a large gain in FM but also by a gain in FFM, the composition of excess weight gain being 70-80% fat and 20-30% FFM 8 (Figure 1).…”
Section: Introductionmentioning
confidence: 72%
“…However, as noted above, a molecular signaling pathway arising from lean tissue cannot be dismissed. Indeed, Cameron et al (115) has recently reported that skeletal muscle mass was a stronger predictor of energy intake (assessed using 3-day food records) than fat-free mass or resting metabolic rate in 304 post-pubertal adolescents. These recent studies on relationships among body composition, resting metabolic rate, total daily energy expenditure and food intake that have been published in the last four years suggest a different biological approach to appetite regulation.…”
Section: Is It Fat-free Mass or Energy Expenditure Per Se That Drivesmentioning
confidence: 99%
“…In regards to homeostatic mechanisms, there have been studies examining changes in gut peptides, inflammatory markers, and substrate or macronutrient utilization as possible factors that influence post-exercise EI (15, 16, 32). In addition, fat-free mass (FFM) is a known predictor of daily EI in adolescents and adults, predominantly through its effects on resting metabolic rate and total energy expenditure (EE) (4, 8, 9, 27). Furthermore, it has been proposed that cognitive factors also contribute to additional variability in daily EI.…”
Section: Introductionmentioning
confidence: 99%
“…FFM is a large determinant of resting metabolic rate, which contributes greatly to total daily EE (2). In addition, FFM has been shown to be a better predictor of EI than FM in both adolescents and adults (3, 8, 9, 27). However, research in younger children is lacking.…”
Section: Introductionmentioning
confidence: 99%